2019
DOI: 10.1039/c9ra00182d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni nanoparticles by liquid-phase reduction to fabricate metal nanoparticle–polyimide composite films

Abstract: Nickel-nanoparticle-containing polyimide composite films were prepared by liquid-phase reduction of Ni2+ ions with potassium borohydride (KBH4). This preparation method could be repeated to increase the number of the nanoparticles in the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Many researchers found that metal nanoparticles (NPs) could catalyze the hydrolysis of KBH 4 and accelerate the generation rate of hydrogen [ 7 , 15 , 16 ]. For example, Kilinc et al [ 7 ] successfully prepared the Pd complex catalysts for promoting the KBH 4 hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers found that metal nanoparticles (NPs) could catalyze the hydrolysis of KBH 4 and accelerate the generation rate of hydrogen [ 7 , 15 , 16 ]. For example, Kilinc et al [ 7 ] successfully prepared the Pd complex catalysts for promoting the KBH 4 hydrolysis.…”
Section: Introductionmentioning
confidence: 99%